Mangrove Wetlands: Vis-A-Vis Biodiversity and Natural Stressors - S. Dam Roy (Journal of Indian Fisheries Association, 2020)
Mangrove wetlands spread across 4975 sq.km of the coastal States and Union Territories of India. West Bengal (2097 Sq km), Gujarat (1103 Sq km), Andaman & Nicobar Islands (604 Sq km), Andhra Pradesh (352 Sq km) and Odisha (213 Sq.km) constitute about 87% of the total mangrove areas of India. These mangrove wetlands are repository of enormous biodiversity of both flora and fauna that need to be conserved in their pristine condition. Mangrove ecosystems are very rich in nutrient and support good growth of phytoplankton and zooplankton and they are also very rich in benthic fauna. This essential quality of mangrove ecosystem, makes it a breeding and nursery ground of many commercially important fin fishes and shell fishes. The paper also deals with the natural stressors like sea surges, cyclone, tsunami etc and how mangroves help in protecting the landward sides by acting as a bio shield. The mitigation of the natural disaster through aquaculture is also discussed. The paper is based on three decades of work on mangrove by the author and is also based on the exposure to the Sundarban area through project based studies.